2013
DOI: 10.1186/1471-2474-14-344
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin K inhibitors increase distal femoral bone mineral density in rapidly growing rabbits

Abstract: BackgroundSelective and reversible inhibitors of human Cathepsin K (CatK), including odanacatib (ODN), have been developed as potential therapeutics for the treatment of osteoporosis. Inhibitors of human CatK show significantly less potency for the rodent enzymes compared with that for the human or rabbit enzymes; thus the Schenk model in growing rabbit was developed as a screening assay for the in vivo activity of CatK inhibitors in blocking bone resorption.MethodsIn this study, the efficacy of the selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…(11) Bone formation is a dominant event during skeletal growth, and ODN increased distal femoral BMD in growing rabbits. (12) Adult mice in which CK gene has been deleted displayed higher mineral apposition and bone formation rates in addition to having higher trabecular and cortical bone mass than their wild-type counterparts. (13) In human bone biopsy samples, CK immunoreactivity was demonstrated in osteoblasts, osteocytes, and lining cells, and CK activity was shown in cultured osteoblasts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(11) Bone formation is a dominant event during skeletal growth, and ODN increased distal femoral BMD in growing rabbits. (12) Adult mice in which CK gene has been deleted displayed higher mineral apposition and bone formation rates in addition to having higher trabecular and cortical bone mass than their wild-type counterparts. (13) In human bone biopsy samples, CK immunoreactivity was demonstrated in osteoblasts, osteocytes, and lining cells, and CK activity was shown in cultured osteoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Five years of continued ODN therapy in a phase 2 study on postmenopausal women with low BMD showed a trend of elevation of procollagen type 1 N‐terminal propeptide (P1NP; a serum marker of bone formation) over the baseline values . Bone formation is a dominant event during skeletal growth, and ODN increased distal femoral BMD in growing rabbits . Adult mice in which CK gene has been deleted displayed higher mineral apposition and bone formation rates in addition to having higher trabecular and cortical bone mass than their wild‐type counterparts .…”
Section: Introductionmentioning
confidence: 99%
“…The human CatK inhibitor ODN is significantly less potent against the rodent enzyme due to the differences between human versus rodent enzymatic sites . Meanwhile, rabbit CatK shares high sequence identity to its human counterpart . Thus, the inhibitors developed against the human enzyme, including ODN, have similar efficacy in blocking the recombinant rabbit CatK and effectively preventing bone loss in the rabbit model of estrogen‐deficiency osteopenia .…”
mentioning
confidence: 99%
“…Meanwhile, rabbit CatK shares high sequence identity to its human counterpart . Thus, the inhibitors developed against the human enzyme, including ODN, have similar efficacy in blocking the recombinant rabbit CatK and effectively preventing bone loss in the rabbit model of estrogen‐deficiency osteopenia . Previously, the rabbit mid‐ulnar osteotomy fracture model has been used to evaluate the therapeutic agent, recombinant human bone morphogenic protein .…”
mentioning
confidence: 99%
See 1 more Smart Citation